MEMPROGRAMKAN PENGENALAN MANAJEMEN PEMASARAN BISNIS SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA KAREHKEL, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Miftakhul Anwar; Muhammad Wildan Fauzi Rahman (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
This community service aims to assist business actors, especially Micro, Small and Medium Enterprises or MSMEs in implementing sharia marketing management for MSME products in Karehkel Village, Leuwiliang District, Bogor Regency. The method of community service activities begins with the preparation stage, field survey and socialization stage. The results of this community service activity added to the participants' knowledge about sharia business marketing management and added confidence to the community in developing businesses on MSME products. After the socialization activities were carried out and the presentation of the material was delivered, it was found that the knowledge of the participants regarding marketing management of sharia business was increasing.